Study on the biochemical function of recombinant delta class drosophila melanogaster glutathione s-transferase 3 (DMGSTD3) / Kithalakshmi Vignesvaran - Kithalakshmi, Vignesvaran (2017)
Insect glutathione S- transferases (GST) have been studied extensively due to their role in insecticide resistance and oxidative stress. The conjugations of the endogenous or exogenous toxins are catalysed by nucleophilic attack provided by side chains of active residues (Tyr, Ser or Cys) located at position 5 or 6 of the N-terminal of the polypeptide. Delta class Drosophila melanogaster glutathione S- transferases D3 (DmGSTD3) has however a truncated N-terminal sequence (15 amino acids) suggesting the absence of the previously mentioned active residue for catalysis. Our study was to characterise the recombinant GSTD3 and investigate the role of the amino acid residue associated to catalysis of GSTD3. DmGSTD3 gene was cloned into the pET-30a and expressed in an Escherichia coli production system. The GSTD3 protein was purified using an anion exchange chromatography. Substrate specificity test showed that the recombinant protein was only reactive towards 1, chloro-2,4- dinitrobenzene (CDNB) (7.3807 μmol/min/mg), a common substrate for GSTs, suggesting a possible involvement of other residues in the polypeptide that contribute to the catalysis. No activity was observed with 1,2-dichloro-4-nitrobenzene, pnitrophenyl chloride, trans-2-octenal, trans-2-hexanal, ethacrynic acid, trans-4-phenyl- 3- butene-2-one, hexa-2,4-dienal, trans,trans-hepta-2,4-dienal, cumene hyperoxide, and hydrogen peroxide. The enzyme activity was optimal at pH 8.2 and at 25° C. GSTD3 enzymatic activity was inhibited by the addition of triphenyltin hydroxide whereas; no difference in activity was detected in the presence of other inhibitors like quercetin, trans- chalcone, tetradecanedioic acid, sebacid acid and triphenyltin acetate. Homology modelling reveals that the side chains of Tyr89 and Tyr97 were facing towards the substrate cavity, proposing their possible role in catalyzing the conjugation. The potential Tyr residues were mutated to alanine via side directed mutagenesis. Specific activity towards CDNB lowered to half when the Tyr89 (3.51 μmol/min/mg) and Tyr97 (3.01 μmol/min/mg) were mutated individually. GSTD3 with Y97A and Y89A gave large changes in Km, Vmax, and Km/Kcat values for GSH as compared to unmutated GSTD3 suggesting the significant role of Tyr89 and Tyr97 in the catalysis of substrate conjugation to GSH in GSTD3. The study has confirmed the limited detoxification function of GSTD3 and the importance of Tyr89 and Tyr97 in GSTD3 catalysis.